Maternal-child nursing care for adolescent mothers: health education - Raquel Dully Andrade; Jeniffer Stephanie Marques Hilário; Jaqueline Silva Santos; José de Paula Silva; Luciana Mara Monti Fonseca; Débora Falleiros de Mello
ABSTRACT Objectives: to develop an educational intervention through a game that addresses aspects related to adolescent motherhood and child care. Methods: this is an action research based on diagnosis, intervention and apprehension stages. Results: the situational diagnosis was based on a literature review on adolescent motherhood and child care. In the intervention stage, the educational game's first version was elaborated. In the third stage constituted by apprehension, the game was submitted to assessment of interdisciplinary experts. Suggestions of experts were adopted and the game had its second version. Final Considerations: the educational intervention in the present study appears a care technology that adds knowledge and practices to the work of nurses in Primary Health Care, focusing on adolescent women and children health care.